Upregulation of outer surface protein c expression by Lyme disease spirochetes in laboratory medium - Olson, Macy (My University, 2015)
Lyme disease is the most common vector borne illness in the United States and there is considerable interest in the ability of vaccination with OspC to provide protection. However, studies to evaluate the efficacy of this approach have been hampered by the lack of OspC expression by spirochetes that have been cultured in traditional Barbour- Stoenner-Kelly (BSK) laboratory growth medium. In this study, I show that maintaining an incubation temperature of 33 C, limiting the number of passages to fresh BSK medium, and adjusting the pH of the culture medium to 6.6, induced the B. burgdorferi ss 297 spirochetes to produce significantly higher levels of OspC. In addition, I developed and used a flow cytometric procedure to confirm that OspC was expressed on the surface of some of the spirochetes. Therefore, additional studies to refine the expression of OspC, so that the Osp is expressed on the surface of each spirochete, remain necessary. However, the findings should help facilitate future efforts to examine the feasibility of OspC-based vaccines.
Keywords: Lyme disease; Biology